Early-life vitamin A supplementation modulates the skeletal muscle transcriptome and intramuscular fat deposition in feedlot-finished beef steers - Baldassini, Welder A [UNESP]; Ramírez-Zamudio, Germán D; Duarte, Marcio S; Ladeira, Márcio M; Pereira, Guilherme L [UNESP]; Machado-Neto, Otavio R [UNESP]; Torres, Rodrigo N S [UNESP]; de Magistri, Murilo S [UNESP]; Camargo, Lucas R [UNESP]; Curi, Rogério A [UNESP]; Chardulo, Luis Artur L [UNESP] (Oxford University Press (OUP), 2025)
This study evaluated the effects of neonatal vitamin A supplementation on intramuscular fat (IMF) deposition and the molecular mechanisms regulating adipogenesis and lipogenesis in Montana × Nellore crossbred beef steers. We hypothesize that neonatal vitamin A supplementation induces long-term transcriptional changes associated with IMF development. Thirty-four calves were randomly assigned to two groups: a control receiving a placebo and a treatment group receiving a single intramuscular injection of 300,000 IU of vitamin A at birth. Longissimus thoracis (LT) muscle samples were collected via biopsy at 40 days of age (cow-calf phase) and again at 400 ± 10 days of age (finishing phase) immediately after slaughter. At deboning (48 hours postmortem), LT samples were collected between the 12th and 13th ribs for chemical composition assessment. Vitamin A supplementation had no significant effect on weaning weight, average daily gain, final body weight, backfat thickness, or ribeye area (P > 0.05). However, IMF content was significantly higher (P < 0.01) in the vitamin A-supplemented (4.10%) compared to control (2.57%). Transcriptomic analysis revealed 52 and 165 differentially expressed genes (DEGs; FDR < 0.05) during the cow-calf and finishing phases, respectively. Functional enrichment analyses showed that vitamin A supplementation upregulated the actin cytoskeleton, insulin, and calcium signaling pathways during the cow-calf phase, and the PI3K-Akt, AMPK, and PPAR signaling pathways during the finishing phase. Notably, key genes associated with adipogenesis and lipogenesis, such as KRAS, ITGB6, CALML6, CISH, and ATF3 in the cow-calf phase, and LEP, ACACA, FASN, SCD, ELOVL6, and CIDEC in the finishing phase, were upregulated in response to vitamin A, as well as several adipogenic regulators, including PPARG, C/EBPA, and FABP4. Pathway enrichment analysis highlighted the PI3K-Akt signaling pathway as a central mediator of vitamin A's effects on adipocyte differentiation and lipid metabolism. Thus, neonatal vitamin A supplementation can enhance IMF deposition in beef steers by modulating key molecular pathways, without negatively impacting growth performance or carcass traits.